Gastrointestinal hemangioma in childhood: a rare cause of gastrointestinal bleeding - Eon Chul Han; Soo-Hong Kim; Hyun-Young Kim; Sung-Eun Jung; Kwi-Won Park (Korean Pediatric Society, 2014)
Gastrointestinal (GI) hemangiomas are relatively rare benign vascular tumors. The choice of an appropriate diagnostic method depends on patient age, anatomic location, and presenting symptoms. However, GI hemangiomas are not a common suspected cause of GI bleeding in children because of their rarity. Based on medical history, laboratory results, and imaging study findings, the patient could be treated with either medication or surgery. Herein, we report 3 cases of GI hemangioma found in the small bowel, rectum, and GI tract (multiple hemangiomas). Better knowledge and understanding of GI hemangioma could help reduce the delayed diagnosis rate and prevent inappropriate management. Although rare, GI hemangiomas should be considered in the differential diagnosis of GI bleeding.